Diálogos carnavalescos: o risco reflexivo em Caim - Triaca, Jessica Valdati (2023)
This study has as literary corpus the novel entitled Caim (2009), written by the Portuguese author José Saramago. The analysis turned to the elaboration of the parodic, carnival and ironic language, which establishes a reflective and questioning laughter when dialogue with scriptural narratives. The studied Bible passages were: Adam and Eve, Cain and Abel, Sodom and Gomorra, Abraham and Isaac, The Job’s sacrifice and the No ah’s Ark. Therefore, the excerpts interpretation aims to compare the narratives and reflect about the esthetic purposes of the Portuguese writer constructions, thus far the only in Portuguese language to be awarded with the Nobel Prize title in literature. In this path we explore the usage of these resources, which establish the dialogue with the readers, expand the reflections about what is serious, dogmatic and holy, such as the Bible narratives. As theoretical sources were used the authors Bakhtin (1996), Fourastié (1985), Minois (2003), Hutcheon (1985-2000), Lopes (2010), Ferraz (2012), Moisés (2004), Alberti (2011), Duarte (2006) and others. The reflections allude to the comprehension which sources, for instance, irony, carnival and parodic laughter, when cause the dethronement of arbitrary things, promote the criticality, autonomy thought and expand the cosmovision. Consequently, the saramaguian narrative, written stem from these mechanisms, causes the emergence of different points of view and possibilities to the bible narrative, as well as for discoursers which occupy serious, sacred and unquestionable places. It was considered which the romance and its reflexive courses add to readers development, whom are provoked to dialogues which potentially expands the ways to understand the world and the discoursers which are in contact with daily life.